Negative Pressure Wound Dressing Reduces Surgical Site Infections in Infants after Closed Abdominal Procedures: A Preliminary Report - Zoeller, Christoph; Yoshizawa, Emi; Sethi, Mohammad V.; Ure, Benno M.; Kuebler, Joachim F. (European Journal of Pediatric Surgery, 2019)
Introduction Negative pressure wound therapy (NPWT) is a novel tool to reduce surgical site infections (SSIs). Although SSIs are a common source of morbidity in infants undergoing laparotomy, the cost of the available NPWT devices has restricted its use to adult high-risk patients. We developed a low-cost method of NPWT in infants and analyzed its impact on the incidence of SSIs in infant patients.Materials and Methods A consecutive series of infants (age ≤ 12 months) who underwent a clean-contaminated, contaminated, or dirty abdominal procedure via laparotomy from 08/2015 to 12/2016 were included. The choice of the applied dressing, either NPWT or standard surgical dressing (SSD), was made at the surgeon's discretion. SSIs were documented prospectively. The Horan definition and the Clavien-Dindo classification were used. The cost of material was calculated for both groups.Results Ninety-three consecutive patients were included (65 SSD and 28 NPWT). SSI occurred in 10 patients in the SSD group, Grade I in 7 and Grade II in 3 (Clavien-Dindo classification). No SSI occurred in patients with NPWT (p < 0.05). The cost of an SSD was less than 1 €, and the cost of a NPWT was less than 10 €.Conclusion The routine use of this modified vacuum wound dressing may be an efficient and affordable technique to decrease SSIs in infants who underwent contaminated abdominal operations.
Keywords: negative pressure wound dressing; surgical site infection; clean-contaminated; contaminated; dirty abdominal procedure; infants